Numerical exploration for structure design and free-energy loss analysis of the high-efficiency polysilicon passivated-contact p-type silicon solar cell. (15th January 2019) - Zeng, Yuheng; Yang, Qing; Wan, Yimao; Yang, Zhenhai; Liao, Mingdun; Huang, Yuqing; Zhang, Zhi; Guo, Xueqi; Wang, Zhixue; Gao, Pingqi; Wu, Chung-Han; Yan, Baojie; et al.
Highlights: p-type solar cell with front-junction and rear-BSF polysilicon passivated contact are studied. Structure design, lifetime, resistivity, passivation and contact resistivity are considered. FELA is used to find out energy loss of passivated contacted p-type solar cell. p-type polysilicon contact serving as rear BSF is more favorable if lifetime of <350 μs. Roadmap toward 23% industrial p-type solar cell with p- or n-type polysilicon contact is proposed. Abstract: In this work, the application of the p-type and n-type polysilicon passivated contact on industrial-level p-type silicon solar cell is studied using numerical simulation. The effects of (i) the structure design, (ii) the bulk lifetime and resistivity of the p-type wafer, and (iii) the carrier selectivity of polysilicon passivated contact on cell performances are investigated. Furthermore, the corresponding energy-loss pathways are classified by using free energy loss analysis (FELA). In essence, the rear-junction solar cell with the n-type polysilicon passivated-contact generates more internal power because of the better surface passivation and less front metallization shading, but the efficiency potential is limited by the low lifetime of the state-of-the-art p-type Czochralski (Cz) wafer. Thus, the p-type polysilicon passivated contact serving as the back-surface field would be more favorable if the lifetime of the p-type Cz silicon were less than 350 μs. Over the long term, the lifetime of the p-type wafer possibly becomes the bottleneck of the high-efficiency polysilicon passivated-contact solar cells. Finally, we present the roadmap toward the 23% industrial p-type silicon solar cell with the p-type or n-type polysilicon passivated contact.